Analisis Pengelolaan Kearsipan Menggunakan Algoritma Machine Learning pada Fakultas Arsitektur Lansekap dan Teknologi Lingkungan, Universitas Trisakti - Endrawan, Afif; Napiah, Musriatun (MES Bogor, 2024)
This research discusses the analysis of archive management using machine learning algorithms, especially the Decision Tree method, at the Faculty of Landscape Architecture and Environmental Technology, Trisakti University. This research aims to improve the efficiency and quality of incoming and outgoing letter archive management. The results showed that the Decision Tree algorithm is effective in managing archive data, facilitating searches, and improving the systematization and efficiency of the archive storage and maintenance process. The implementation of this algorithm is proven to have a positive and significant effect, so the working hypothesis stating the positive effect of this algorithm on archive management is accepted, while the null hypothesis is rejected.